Shooting Stars Heroes and Heroines of Western Film - McDonald, Archie P. (Indiana University Press, 1987)
Since the first moving pictures, no one genre of film has captured the hearts of Americans as has the Western. In Shooting Stars, Archie McDonald, scholar and self-confessed cowboy hero worshipper, presents a rich, informative array of essays on our favorite Western stars. These twelve contributions by established scholars of Western film review the biographical and cinematic lives of stars from the 1920s to the present; together, they constitute a unique collection and a fitting tribute to the influence of these heroes on our lives.